Beyond the big city: using a systems approach to cultivate a cycling culture in small cities and towns in Ireland - Corr, Caitriona; Murphy, Niamh; Lambe, Barry (Frontiers in Sports and Active Living, 2023)
Urban mobility and how people move in our towns and cities, is garnering more attention, as solutions are sought to multiple challenges faced by towns and cities; health and physical inactivity, climate change, air quality, urbanisation and accessibility. Traditional, siloed approaches limit impact and collaborative, systems approaches hold promise. However, systems mapping often remains theoretical and few practical applications of it’s added value have been demonstrated. This action research seeks to illustrate how a systems approach can be used to develop solutions for action on active mobility and enhance sense of place in an Irish town in a pragmatic manner. The systems approach utilises broad stakeholder engagement to map the variables that influence cycling in smaller cities and towns and identify the leverage points for transformational interventions.